RELATIONSHIP BETWEEN RESTRICTIVE STRATEGIES OF PARENTAL CONTROL AND DIGITAL VIOLENCE IN ADOLESCENCE - Matović, Milica; Zunić Pavlović, Vesna (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2021)
Modern studies show that children and adolescents represent the population of users who spend the most time online and that are significantly more exposed to risk behaviors, mostly in cyberbullying. Therefore, the aim of this paper is to determine the effectiveness and frequency of using restrictive strategies in parental control over a child’s online activities. The survey sample contains 183 first and fourth grade high school students answering questions about parental monitoring and cyberbullying. Parental monitoring was examined by a short questionnaire consisted of several categorical questions, while the Cyber ​​Victim and Bullying Scale was used to examine cyberbullying. The results of this study show that parents infrequently use restrictive strategies in monitoring child’s internet use. Parents use their strategies mostly to avoid child’s chatting with strangers (51.9%) and leaving personal information on the Internet (35.5%), while certain parents have a password of the devices that child uses to access the Internet (37.2%). Only one in five parents limit access to certain websites, while one in ten limit amount of time their teen can go online. The final analysis showed that there is no statistically significant association of restrictive strategies in parental control and digital violence. Parental control can become a significant role in preventing and reducing digital violence in adolescents, but it is necessary to direct parents to make decisions about online rules of conduct in agreement with children and in accordance with their activities and encourage them to use other, adequate parental control strategies.